1988
DOI: 10.1113/jphysiol.1988.sp017152
|View full text |Cite
|
Sign up to set email alerts
|

Role of the human fusimotor system in a motor adaptation task.

Abstract: SUMMARY1. Single-unit activity was recorded with the microneurographic technique from the radial nerve of attending human subjects. During active finger movements, impulses in spindle afferents from the extensor digitorum muscle were analysed along with joint movements, size of imposed load and EMG activity of the receptor-bearing muscle.2. In a simple motor adaptation task the subjects were requested to perform ramp-and-hold movements of prescribed amplit-ades and velocities at a single metacarpo-phalangeal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The present findings are consonant with several previous microneurography recordings from spindle afferents in the upper and lower limb in that it failed to demonstrate gamma independence while, in other studies, minute indications of a faint gamma dissociation were occasionally found in a small minority of the spindle afferents recorded (Burg et al 1973(Burg et al , 1974Burke et al 1980a, b;Hagbarth 1981;Vallbo and Hulliger 1981;Gandevia and Burke 1985;Al-Falahe and Vallbo 1988;Aniss et al 1988Aniss et al , 1990aVallbo and Al-Falahe 1990;Gandevia et al 1994;Nielsen et al 1994;Wessberg and Vallbo 1995;Kakuda et al 1996). As a summary of microneurography studies on the issue of gamma independence, it seems fair to conclude that clear evidence of major and consistent fusimotor resetting has not been identified in man except when subjects increase or decrease the amount of extrafusal contraction in the parent muscle.…”
Section: Fusimotor Independence: Difference Between Findings From Behsupporting
confidence: 77%
See 1 more Smart Citation
“…The present findings are consonant with several previous microneurography recordings from spindle afferents in the upper and lower limb in that it failed to demonstrate gamma independence while, in other studies, minute indications of a faint gamma dissociation were occasionally found in a small minority of the spindle afferents recorded (Burg et al 1973(Burg et al , 1974Burke et al 1980a, b;Hagbarth 1981;Vallbo and Hulliger 1981;Gandevia and Burke 1985;Al-Falahe and Vallbo 1988;Aniss et al 1988Aniss et al , 1990aVallbo and Al-Falahe 1990;Gandevia et al 1994;Nielsen et al 1994;Wessberg and Vallbo 1995;Kakuda et al 1996). As a summary of microneurography studies on the issue of gamma independence, it seems fair to conclude that clear evidence of major and consistent fusimotor resetting has not been identified in man except when subjects increase or decrease the amount of extrafusal contraction in the parent muscle.…”
Section: Fusimotor Independence: Difference Between Findings From Behsupporting
confidence: 77%
“…In human subjects, on the other hand, only minute, often dubious, changes of spindle firing rates have been found in a small minority of afferents, except when the parent muscle contraction is adjusted (Burg et al 1973(Burg et al , 1974Burke et al 1980a, b;Hagbarth 1981;Vallbo and Hulliger 1981;Gandevia and Burke 1985;Al-Falahe and Vallbo 1988;Aniss et al 1988Aniss et al , 1990aVallbo and AlFalahe 1990;Gandevia et al 1994;Nielsen et al 1994;Wessberg and Vallbo 1995;Kakuda et al 1996). In contrast, one single study based on recordings from presumed gamma-efferents suggests that substantial fusimotor adjustments occur with various manoeuvres (Ribot et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the reflex response has been shown to increase in proportion to the level of preexisting tonic muscle activation (Gottlieb and Agarwal, 1979;Al-Falahe and Vallbo, 1988), which is often greater for novel tasks involving unstable loads due to the coactivation of agonist and antagonist muscles (De Serres and Milner, 1991;Osu et al, 2002). In an attempt to minimize the effects of coactivation on tonic activity of the first dorsal interosseus muscle, all subjects practiced the MVC, force, and position tasks during a familiarization session 1-3 days prior to the experiment.…”
Section: Delivery Of Mechanical and Electrical Stimulimentioning
confidence: 99%
“…The finger splint which immobilized the interphalangeal joints of the test finger was connected by a hinged bar of low mass to a computer-controlled actuator which has, in part, been described elsewhere (Hulliger, Nordh & Vallbo, 1982;Al-Falahe & Vallbo, 1988 (Edin & Vallbo, 1987 (Matthews, 1972).…”
Section: Actuatormentioning
confidence: 99%